Numeracy Literacy Skills of Introverted and Extroverted Students in Solving Linear Program Problems - Muhammad Hilmi Zakaria; Noviana Dini Rakhmawati; Dhian Endahwuri; Arif Wibisono (Hipotenusa : Journal of Mathematical Society, 2023)
This study aims to determine the numeracy literacy skills of introverted and extroverted students in solving linear programming problems. The method used in this research is descriptive qualitative. The subjects taken were two students of class XI MIPA-2 MA Banat Tajul Ulum Brabo with details of one introvert student and one extrovert student. Data collection techniques were carried out using questionnaires, written tests, and interviews. Retrieval of research data through written tests and interviews. Based on the results of this study, it shows that introverted subjects fulfill all indicators of numeracy literacy skills, namely solving problems using various numbers and symbols related to mathematics; analyze the information presented in various descriptions (graphs, tables, charts, diagrams and so on); and trap the results of that analysis to make predictions and decisions. Meanwhile, the extrovert subject did not fulfill one of the three indicators of numeracy literacy, namely the confidentiality of the results of the analysis to make predictions and decisions.